Protektivitas Sapi di Kabupaten Kupang Terhadap Penyakit Ngorok (Septicaemia Epizootica) (PROTECTIVITY AGAINST SEPTICAEMIA EPIZOOTICA OF COWS IN KUPANG DISTRICT) - Berek, Hilda Susiyanti Debora; Nugroho, Widagdo Sri; Wahyuni, Agnesia Endang Tri Hastuti (Jurnal Veteriner, 2015)
Controlling SepticemiaEpizooticae (SE) through vaccination program has been undertaken in KupangDistrict. However, numbers of fatal cases is still being reported. A cross sectional study have been undertakenin order to determine the prevalence and factors affecting herd immunity at farm level in Kupang District.A total of 434 cow’s sera from 87 farmers were collected and further analyzed using Enzyme-linkedImmunosorbent Assay (ELISA). An antibody titer of e”200 ELISA Unit was used as the indicator ofprotective immunity. The prevalence of herd immunity was 73.7% and vaccination coverage was 90.8%.Based on unweighted logistic regression analysis it was found that factors affecting the animals protectiveimmunity were: animal >2 years of age (r = +1.45601; OR = 4.3); housing system ( r = +1.03958; OR = 2.8);reservoir animals (r = +0.090147; OR = 2.5), the sex of the animal (female) (r = + 0.080138; OR =2.2); oncefrequency of vaccination (r = +0.61015; OR = 1.8); and 6-12 months post vaccination period (r = + 0.58968;OR = 1.8). Based on linier regression analysis, the prevalence of herd immunity was increased during rainyseason, whereas it was decreased when cows werebought from animal market or from other district.
Keywords: prevalence, herd immunity, SepticemiaEpizooticae, risk factors